The Influence of Customer Satisfaction on Customer Loyalty and Marketing Organization Performance Over Outdoor Advertising Companies - Made Ngurah Aditya Paramartha; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
The competition in the advertising industry today is very tight due to the choice of media in advertise is increasing with their respective advantages. To face this competition, the press advertising cannot rely on sales ordinarily but also a more approach to consumers. In this case, the brand which has an interest over promotion market. Thus, this study aims to determine the effective effect on influence of customer satisfaction with customer loyalty and the performance of marketing organizations over outdoor advertising companies. This research uses quantitative research methods to obtain the result. Here, we distribute a document set of questionnaires to collect data from respondents. The manager of advertising agency has interviewed because they are consultants for brands to carry out promotional strategies in advertising in Jakarta, Indonesia. In this research, we obtain the interviewed respondent around 37 people with positions equivalent to media Manager or Media Director in several advertising agencies. Furthermore, this research is processed using the SmartPLS application to obtain the result. The results of this study indicate that customer satisfaction has a significant effect on customer loyalty and organizational performance for the total effect obtained from organizational performance from the application of customer satisfaction by 34.3% which means significant, because that customer satisfaction must always be considered by the company